الذكاء الوجداني وعلاقته بالرضا عن الحياة والتحصيل الأكاديمي لدى طالبات جامعة الجوف - محمد، عالية الطيب حمزة (جامعة القصيم, 2020)
هدفت الدراسة إلى معرفة العلاقة بين الذكاء الوجداني والرضا عن الحياة والتحصيل الدراسي، لدى طالبات جامعة الجوف، كشف الفروق بينهم، ومعرفة الفروق بينهم تبعا للفرق الدراسية. وتمثل مجتمع الدراسة في طالبات كلية التربية، حيث بلغ حجم العينة (93) طالبة، وهي عينة متاحة من الطالبات. وتوصلت الدراسة إلى مجموعة من النتائج أهمها: توجد علاقة ارتباطية إيجابية دالة بين الذكاء الوجداني والرضا عن الحياة، والتحصيل الدراسي، كما توجد علاقة ارتباطية إيجابية دالة بين الذكاء الوجداني والتحصيل الدراسي، وعدم وجود فروق دالة إحصائيا في الذكاء الوجداني والرضا عن الحياة والتحصيل الدراسي، ووجود فروق دالة إحصائيا في الذكاء الوجداني تبعا للفرق الدراسية لصالح طالبات الفرقة الثالثة، وعدم وجود فروق دالة إحصائيا في الرضا عن الحياة تبعا للفرق الدراسية الثالثة والرابعة. وفي ضوء ما توصلت إليه الدراسة من نتائج خلصت الباحثة إلى مجموعة من التوصيات والمقترحات.
The study aimed at finding out the relationship between emotional intelligence, life satisfaction, and achievement, and revealing the differences between them, depending on the class difference. The study sample was (93) female students of the Faculty of Education, which was an available sample. The study reached a number of results, the most important of which are: There is a positive relationship between emotional intelligence, satisfaction with life and academic achievement. There is a positive relationship between emotional intelligence and scholastic achievement. There is no significant correlation between emotional intelligence, satisfaction and achievement. There are statistically significant differences in emotional intelligence according to the study difference for the third-year students, and the absence of statistically significant differences in satisfaction with life among students with high academic achievement and low achievement. In light of the results of the study, the researcher summarized a set of recommendations and suggestions.
Keywords: التحصيل الأكاديمي -- علم النفس الايجابي -- الصحة النفسية